How team leaders can improve virtual team collaboration through trust and ICT: A conceptual model proposition - Kauffmann, David (Economics and Business Review, 2015)
The purpose of this paper is to present a conceptual model to facilitate the development of collaboration within virtual teams. The model claims that a high level of communication through ICT is an important antecedent for collaboration mediated by the level of trust among the team. Furthermore and according to the model, Team Leaders can have a major impact on the communication effectiveness and on the level of team trust.